2009
DOI: 10.1111/j.1600-051x.2008.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand instrumentation versus ultrasonic debridement in the treatment of chronic periodontitis: a randomized clinical and microbiological trial

Abstract: Both treatment modalities provided comparable clinical results in the treatment of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 59 publications
7
71
0
14
Order By: Relevance
“…Nevertheless, at the 4-6 mm sites, SUPRA determined a PPD reduction of 1.09 mm. This mean reduction is similar to that reported by Ioannou et al,17 who observed a 1.28 mm reduction using ultrasonic devices at the subgingival area. In the 7+ mm sites, the reductions in PPD (3.59 mm) and CAL (2.87 mm) observed for the SRP and S30SRP groups together are comparable to those reported by Santos et al 16 with systemic antibiotics (3.48 mm and 2.82 mm, respec- tively).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, at the 4-6 mm sites, SUPRA determined a PPD reduction of 1.09 mm. This mean reduction is similar to that reported by Ioannou et al,17 who observed a 1.28 mm reduction using ultrasonic devices at the subgingival area. In the 7+ mm sites, the reductions in PPD (3.59 mm) and CAL (2.87 mm) observed for the SRP and S30SRP groups together are comparable to those reported by Santos et al 16 with systemic antibiotics (3.48 mm and 2.82 mm, respec- tively).…”
Section: Discussionsupporting
confidence: 91%
“…10,14,26 Some studies showed better results in terms of full-mouth CAL gain when compared with our study. 12,27 These disparities in the gain of attachment level are based on differences in the initial probing pocket depth. As the probing pocket depth increases without gingival recession, the clinical attachment gain increases after proper periodontal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, in several studies, there was a significant decrease in the probing depth and bleeding upon probing and an increase of clinical attachment gain in patients with severe periodontitis treated with both VUS and hand instruments. [12][13][14] Numerous studies have demonstrated decreased levels of TNF-α following the non-surgical periodontal treatment performed with the hand instruments. 15,16 In the literature, there are no reports associated with the effects of vector ultrasonic system on the concentration of inflammatory mediators in patients with periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic scalers were first designed for gross supragingival scaling and removal of stains, but recently, by modification of the diameter and length of the tips, they have become a routine part of scaling and root planing (SRP) procedure [23,24]. Ioannou et al (2009) have been found that both treatment modalities (hand and ultrasonic) provided comparable clinical results and significant reduction of the pathogens in the treatment of chronic periodontitis [6].…”
Section: Antibacterial Effect Of the Conventional Instrumentsmentioning
confidence: 99%
“…This thin, initial biofilm has been almost always present on the tooth surface as it forms immediately after cleaning [2]. An initial few layers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) of the biofilm consist mostly gram-positive cocci bacteria, followed by some gram-positive rods and filaments, and a very small amount of gram-negative cocci. The gram-positive cocci species involved in this conditioning layer include, but are not limited to, S t re p t o c o c c u s m u t a n s , S t r e p t o c o c c u s m i t i s , Streptococcus sanguis, Streptococcus oralis, Rothia dentocariosa, and Staphylococcus epidermidis.…”
Section: Introductionmentioning
confidence: 99%